If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(-1 + m) = -7m + -3 (-1 * 3 + m * 3) = -7m + -3 (-3 + 3m) = -7m + -3 Reorder the terms: -3 + 3m = -3 + -7m Add '3' to each side of the equation. -3 + 3 + 3m = -3 + 3 + -7m Combine like terms: -3 + 3 = 0 0 + 3m = -3 + 3 + -7m 3m = -3 + 3 + -7m Combine like terms: -3 + 3 = 0 3m = 0 + -7m 3m = -7m Solving 3m = -7m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '7m' to each side of the equation. 3m + 7m = -7m + 7m Combine like terms: 3m + 7m = 10m 10m = -7m + 7m Combine like terms: -7m + 7m = 0 10m = 0 Divide each side by '10'. m = 0.0 Simplifying m = 0.0
| 4/9y=8/3 | | 8y=x+64 | | 6+925=459696 | | 1/8+13/32 | | 2(x+8)=x-6 | | x^(3/2)=8000 | | 9x-173=52-6x | | 4p+13=21 | | -3k+8-4k=57 | | 15x-12=y | | 78x+2=9x+20 | | -5x+11y=3 | | (7n-7)-(7-6n)= | | 300/10= | | -11+9x=21+7x | | 55t+28=32-50t | | .6b+5=.75 | | 2c+10+c+2=-90 | | x(5x-8)-2(5x-8)=0 | | 25y-4=2y+8 | | 5y=20x-5 | | 7d-3d-6=-6 | | 12+3m=2-7m | | 15x^3+10x=0 | | 6(n-2)=7n-5 | | 15x-12= | | -36+7x=3x+12 | | log(3x)=0.76 | | 9k-3=5k+7 | | ln(x-3)+ln(3x+1)=8 | | 0=(1/6)y+8 | | 31/2c+21/2c=54 |